Peace Linguistics in the Academic Community Through the Lens of English Language Teachers: A Multiple Case Study - Baisoraya Sampiano Parcon; Teresita Q. Adriano (Randwick International of Education and Linguistics Science Journal, 2024)
This qualitative multiple case study delves into the English Language Teachers’ integration and assessment of peace linguistics in various pedagogical practices, focusing on the exploration of both violent and nonviolent terminologies expressed by students in classroom setting. Data collection involved in-depth interviews with five ELTs, triangulated to two additional teachers and five students. The data were thematically analyzed, revealing five essential themes for violent and nonviolent phraseologies and terminologies expressed by students such as: Moralistic Judgement expressions, cultural and religious expressions, positive and encouraging language, promotion of peaceful communication and teamwork, and the use of courteous language. Second, it uncovers five emergent themes in the incorporation of peace linguistics: promoting inclusive and peaceful language, cultivating a culture of peace through interactive pedagogy, incorporating culturally inclusive teaching materials, sustaining peace linguistics across the subject, collaborating efforts with peer teachers or experts. Third, it highlights four essential themes in gauging success in ELTS pedagogy: assessment of peaceful efficacy, peace pedagogy feedback methods, changes in students' behavior positively, and engagement in peace awareness professional development opportunities. The cases imply both similarities and differences in how ELTs incorporate peace linguistics into their classes and gauge their success, despite encountering both violent and nonviolent expressions among students.